Routledge handbook of European politics - Magone, José M. (José María) 1962 (Routledge, Taylor & Francis Group, 2014)
"Since the Treaty of the European Union was ratified in 1993, the European Union has become an important factor in an ever-increasing number of regimes of pooled sovereignty. This Handbook seeks to present a valuable guide to this new and unique system in the 21st century, allowing readers to obtain a better understanding of the emerging multilevel European governance system that links national polities to Europe and the global community. Adopting a pan-European approach, this handbook brings together the work of leading international academics to cover a wide range of topics such as: o the historical and theoretical background o the political systems and institutions of both the EU and its individual member nations o political parties and party systems o political elites o civil society and social movements in European politics o the political economy of Europe o public administration and policy-making o external policies of the EU. This is an invaluable and comprehensive resource for students, scholars, researchers and practitioners of the European Union, European Politics and Comparative Politics"-- Provided by publisher.